PELAKSANAAN JUAL BELI KARET DAN KELAPA SAWIT PARA PETANI OLEH TOKE DI DESA KARANG TENGAH BENGKULU UTARA MENURUT ISLAM - Marini Marini; Dharma Setiawan; Wahid Dedi Fauzi (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2022)
Rubber and oil palm plantations are the backbone of the people's economy in Karang Tengah village. The development of the rubber and oil palm plantation sectors has a positive impact on the economic growth of a region. The community in fulfilling the necessities of life is always buying and selling. Because, buying and selling is an effort of the people of Karang Tengah village in meeting their daily needs. Basically buying and selling is made lawful by Allah SWT. Toke plays an active role in helping the continuity of the sale and purchase of farmers in Karang Tengah Village in accordance with the initial agreement that was agreed between Toke and Farmers in Karang Tengah Village with the principle of kinship and is happy and happy without anyone feeling disadvantaged by the agreement, the factors - The factors inhibiting buying and selling are: transportation and traffic facilities, distant factory locations, payment delays, and prices that tend to fluctuate. Buying and selling in Karang Tengah Village is in accordance with the Sharia Agreement because it has followed the applicable rules in accordance with the sharia contract, but farmers and toke do not know this.